NanoSIMS sulfur isotope studies of pyrite from the Early Paleozoic marine shale: Implications for the sedimentary environment. (February 2021) - Zuo, Quanwen; Xu, Yanran; Yu, Bingsong; Zhang, Cong; Zhang, Yifan; Hou, Changhai; Zhang, Linhao; Sun, Mengdi
Abstract: The presence of pyrite has been reported previously in the Longmaxi and Niutitang Formations in southern China, and can serve as an important indicator of the sedimentary environment. In order to systematically investigate the differences between the paleoenvironments of samples from the two formations, complementary experiments were conducted on six samples from the same well (three from each of formations). The methods included nano-scale secondary ion mass spectrometry (NanoSIMS) for in situ sulfur isotope analysis, isotope ratio mass spectrometry (IRMS) for comparison with the data from NanoSIMS, field emission scanning electron microscopy (FE-SEM) to observe the pyrite forms, inductively coupled plasma mass spectrometry (ICP-MS) for the analysis of trace elements, LECO carbon/sulfur analyzer for determining the total organic carbon (TOC) content, and X-ray diffraction (XRD) to identify the mineral compositions. The results suggest that NanoSIMS can analyze submicron pyrite grains visually, which could help to differentiate euhedra and framboids during the analyses. The sulfur isotope ratios inside the framboidal pyrite analyzed by NanoSIMS suggest that the formation of the framboidal pyrite occurs from the center to the surface, as against the assumed process wherein iron non-sulfide spheroids are pseudomorphically replaced by pyrite. The size distribution of the framboidal pyrite and the redox-sensitive trace elements of the bulk rock jointly indicate that the bottom water redox conditions of the Niutitang Formation were reduced more compared those of the Longmaxi Formation. The sulfur isotopic characteristics of the framboidal pyrite imply that the two formations were deposited in an open sedimentary system (a depositional system where sulfate radical ions could diffuse into the system from the external environments); in this regard, the Niutitang environment was found to be progressively closing while the Longmaxi environment was found to be gradually opening. Highlights: The effectiveness of NanoSIMS and the bulk-rock sulfur isotope analysis for testing submicron pyrite was compared. A geochemistry evidence for formation processes of the framboidal pyrite was proposed. Progressive change patterns of paleoenvironments were established based on in-situ submicron sulfur isotope ratios.